2007
DOI: 10.1002/iroh.200610916
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Fire Exposed Eucalyptus Leaves in a Portuguese Lowland Stream

Abstract: We compared fire exposed with normal abscised eucalyptus leaves incubated in a stream running through eucalyptus plantations in central Portugal, in terms of breakdown rates, microbial activity, diversity and macroinvertebrate abundance. Although leaves exposed to fire had lower nutritional value, mass loss was similar for both leaf types (k = 0.0089 -0. for normal leaves). Fungal biomass was similar among treatments, whereas sporulation and microbial respiration were lower in fire exposed leaves. Both leaf ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…Webster et al [57] described T. elegans as a seasonal antagonist of L. curvula appearing in England only during the warmer months, but our results have shown that conidia of both species appear simultaneously in relatively high densities in several streams, T. elegans being dominant since very early stages and L. curvula appearing later. Gama et al [27] found an alternation between these two taxa in a Portuguese stream during leaf decomposition, L. curvula being the dominant species in late phases. Finally, A. tetracladia dominated conidial production in one of the streams studied, confirming previous findings of heavily sporulation of this species [22,23,36,39].…”
Section: Aquatic Hyphomycete Community Variability and Leaf Litter Prmentioning
confidence: 98%
“…Webster et al [57] described T. elegans as a seasonal antagonist of L. curvula appearing in England only during the warmer months, but our results have shown that conidia of both species appear simultaneously in relatively high densities in several streams, T. elegans being dominant since very early stages and L. curvula appearing later. Gama et al [27] found an alternation between these two taxa in a Portuguese stream during leaf decomposition, L. curvula being the dominant species in late phases. Finally, A. tetracladia dominated conidial production in one of the streams studied, confirming previous findings of heavily sporulation of this species [22,23,36,39].…”
Section: Aquatic Hyphomycete Community Variability and Leaf Litter Prmentioning
confidence: 98%
“…De facto, em quatro locais ao longo de um gradiente de degradação no rio Ave, os fungos aquáticos contribuíram para 74-90% da massa perdida devido à atividade microbiana enquanto as bactérias contribuíram para 10-26%, i.e., 3-9 vezes menos 13 . A atividade reprodutiva dos hifomicetes aquáticos, i.e., a produção de esporos (Figura 12.4a-c), incorporou até 7% da massa inicial de folhas de carvalho incubadas durante 85 dias no ribeiro da Mata da Margaraça 22 , até 10% da massa inicial de folhas de carvalho incubadas durante 63 dias na Ribeira do Botão 23 e até 10% da massa inicial de folhas de eucalipto incubadas durante 90 dias no mesmo ribeiro24 . No entanto, a maior parte da massa das folhas é convertida em micélio (biomassa fúngica) ou é mineralizada25,26 .A atividade dos microorganismos (i.e., a sua respiração, crescimento e reprodução) nas folhas inicia-se logo após a colonização, até um pico15,17,21,27,28 (Figura 12.4d) cuja magnitude e tempo que demora a ser atingido dependem da identidade das folhas e das condições ambientais (p.ex., temperatura, concentração de nutrientes, presença de contaminantes), sendo geralmente mais elevado e rápido para folhas moles e ricas em nutrientes (p.ex., folhas de amieiro) e quando a concentração de nutrientes na água é moderada15,17,22 (Figura 12.4d).…”
unclassified
“…(sensu Hoffmann and Hering 2000). Like Gama et al (2007), we suggest that invertebrates colonizing wood may use it more as substratum than as food. Our results showed that fire-induced changes in quality of allochthonous inputs per se may not alter the structure of macroinvertebrate communities.…”
Section: Discussion Burned Stream Wood and Macroinvertebratesmentioning
confidence: 99%
“…For example, Mihuc and Minshall (1995) found that only 1 macroinvertebrate taxon was able to grow when fed burned organic matter. In addition, Gama et al (2007) reported a reduction in nutritional quality of fire-exposed leaves relative to normal eucalyptus leaves in a central Portugal stream. However, the diversity and macroinvertebrate abundance were similar between treatments ).…”
Section: Discussion Burned Stream Wood and Macroinvertebratesmentioning
confidence: 99%